EVALUATION OF OPTIMAL TIME AND PREGNANCY TERMINATION MODALITIES IN PATIENTS WITH DIABETES MELLITUS - Gabbassova, Saniya (Nazarbayev University School of Medicine, 2024)
Background: The poor management of diabetes mellitus (DM) type 1, type 2, and gestational diabetes in pregnant patients is associated with higher risk of adverse outcomes affecting both maternal and neonatal health. Therefore, to reduce the risk of adverse pregnancy outcomes, it is important to determine appropriate time and mode of delivery in patients with DM. Methods: This retrospective cohort study included 281 patients with diabetes mellitus delivered between 2013-2017. Patients were divided into five groups based on the weeks of gestation at delivery: <37w, 37-37(+6)w, 38-38(+6)w, 39-39(+6)w, and 40-41 weeks. Additionally, based on the mode of delivery: vaginal delivery, cesarean section, induced vaginal delivery, and emergency cesarean section. Results: Out of 281 patients 49 (17.44%) delivered < 37 weeks and at 37-37(+6)weeks, 63 (22.42%) patients delivered at 38-38(+6)weeks, 82 (29.18%) patients at 39-39(+6)weeks, and 38 (13.52%) patients delivered at 40-41weeks of gestation. According to the mode of delivery, 62 (22.78%) patients had vaginal delivery, 145 (51.60%) had planned cesarean section, 45 (16.01%) patients had induced vaginal delivery, and 27 (9.61%) patients had undergone emergency cesarean section. Patients with preeclampsia (OR 10.73[4.90, 23.55]), chronic hypertension (OR 2.25 [1.17, 4.32]), diabetic nephropathy (OR 4.06 [2.02, 8.18]), and pathologic CTG (OR 5.06 [2.61, 9.80]) were more likely to deliver before 37 weeks. In neonates born preterm the odds of Apgar score < 7 at 5 min (OR 5.06 [1.22, 21.00]), resuscitation (OR 7.84 [3.62, 16.96]), intubation of the lung (OR 4.67 [1.61, 13.56]), use of oxygen mask (OR 7.84 [3.62, 16.95]), broncho-pulmonary disease (OR 4.83 [1.76, 13.26]), and other diseases (OR 3.44 [1.71, 6.93]) were higher. The macrosomia was 2.38 times more likely in babies born at 40-41 weeks. Neonates born at 38-38(+6)w and 39-39(+6)w groups were less likely to have resuscitation (OR 0.13 [0.03, 0.56]), use of oxygen mask (OR 0.06 [0.01, 0.46]). In terms of mode of delivery, in DM type 2 the odds of having emergency CS were 2.68 times higher. The PROM was associated with vaginal delivery, and pathologic CTG with emergency CS (OR 2.50 [0.16, 5.36] and OR 2.76 [1.21, 6.32], respectively). The use of oxygen mask was less likely in babies born by vaginal delivery (OR 0.19 [0.04, 0.80]). Conclusion: The delivery at 39th week of gestation was common. Participants mostly delivered by cesarean section. Patients with obstetric complications had higher rates of preterm delivery. Neonates born before 37th week were more likely to develop complications. Macrosomia was more common in babies born at 40-41 weeks. Among neonates born at 38th and 39th week resuscitation was less common. Patients with type 2 DM had higher rates of emergency CS. Except for the use of oxygen mask, there was no association between neonatal complications and mode of delivery. Recommendations: Based on results of the study, for achieving favorable neonatal outcomes the delivery at 38-38(+6) weeks or 39-39(+6) weeks of gestation is recommended.
Keywords: type of access: gated access